Team Approach: Rehabilitation Strategies for Patients After Osteosarcoma Reconstructive Surgery. Issue 10 (October 2020) - Kim, Tae Won B.; Kumar, Rohini Johar; Gilrain, Kelly L.; Kubat, Emily; Devlin, Caitlyn; Honeywell, Samantha; Amin, Sheena J.; Gutowski, Christina J.
Abstract : The multimodal treatment of osteosarcoma with chemotherapy, surgical resection, and reconstruction has improved outcomes after a limb-salvage surgical procedure. Physical rehabilitation considerations after surgical resection vary, depending on the location of the tumor. Physical medicine and rehabilitation physicians incorporate lymphedema specialists, orthotists, and prosthetists to help to improve limb function. Beyond physical rehabilitation, psychological or behavioral interventions and nutritional rehabilitation are necessary to maximize a patient's return to function.